Short-term variations of parameters of heart rate variability in subjects with mild hypertension and normotensive subjects during preoperative period - Meldijana, Omerbegovic (CMBEBIH 2017, 2017)
Monitoring of heart rate variability that could reflect autonomic nervous system tone might be of clinical importance in subjects who are scheduled for elective surgical treatment.Individuals with balanced autonomic nervous system tone in the situations of increased demands and stress load have been shown to have preserved hemodynamic reserve which is very important for hemodynamic stability. On the contrary, individuals who had developed some alterations of autonomic nervous tone as a result of different physiological changes have shown predisposition to inadequate hemodynamic adaptability to different stressful conditions and surgical procedure as a possible major stressful event.The aim of the trial was to estimate the parameters of heart rate variability in time and frequency domain for subjects scheduled for elective surgical procedures. Thirty-six subjects were allocated to two groups. Individuals who had developed mild hypertension were allocated to first group while normotensive individuals constituted the second group. Recordings of electrocardiogram were analyzed in time domain : SDNN (standard deviation of NN intervals), RMSSD (root mean square of the successive differences), and in frequency domain: power of the total spectrum of heart rate variability(TP),power of low frequency band (LF, range 0,04-0,15Hz), power of high frequency range(HF, range 0,15-0,4 Hz). Analysis of the values of hemodynamic parameters has shown different hemodynamic parameters but no significant statistical differences were found between the groups. Analysis of the values of time-domain and frequency-domain parameters of heart rate variability has shown variations of the SDNN, RMSSD and parameters of total spectrum power and LF and HF spectra while no statistically significant difference was found. The results have shown variations of time-domain and frequency-domain parameters of heart rate variability in individuals with mild hypertension and normotensive individuals, but for this specific groups of patients there was no statistically significant difference.